The New Code of Ethics: Implications for Perioperative Nurses - Balcom, Corina (Operating Room Nurses Association of Canada Journal, 1994)
This article will look brieﬂy at the historical development of the Code of Ethics for Nurses and then critique the New Code of Ethics. From there, aspects of the Code will be applied to perioperative nursing. The Canadian Nurses Association (CNA) revised its Code of Ethics of Nursing to all its members in November, 1992. Nurses can be guided by this document in ethical issues which they must face in their work. Perioperative nurses encounter specific situations daily, for which the Code of Ethics can be a guide.